Neural evidence of deprioritizing to-be-forgotten information in visual working memory - Moen, Katherine C.; Beck, Melissa R.; Horner, Scarlett; Greening, Steven G. (Frontiers in Cognition, 2024)
Although evidence supports the effective use of a cue to forget an encoded stimulus, the mechanisms of this forgetting are not well understood. Evidence from item-method directed forgetting in long-term memory reveals greater prefrontal and parietal activation for information that is cued to be forgotten. Activation in those brain regions is typically associated with increased effort and cognitive control. To test the mechanism of directed forgetting in visual working memory, we used stimuli that rely on distinct brain regions such as faces and buildings and varied memory stability. Participants completed a directed forgetting task with faces and buildings, and memory stability was manipulated by presenting some stimuli repeatedly throughout the study, and other stimuli were only presented once. Functional magnetic resonance imaging (fMRI) results from the parahippocampal place area suggest that to-be-remembered buildings elicit higher activation than to-be-forgotten buildings. In addition, dorsolateral prefrontal cortex activation changed throughout the trial period, possibly suggesting that the cue led to information being dropped from visual working memory, or through a shift in attention, as occurs with the retro-cue paradigm. Several explanations for these results are discussed.